PENGARUH KEPEMIMPINAN, MOTIVASI, LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI KONTRAK SEKRETARIAT KANTOR WALIKOTA DENPASAR - Saputra, Anak Agung Gede Dharma; Rahyuda, Agoes Ganesha (E-Jurnal Manajemen; Vol 7 No 5 (2018), 2018)
Secretariat of Denpasar Mayor Office is a government institution directly related to public service in Denpasar city, so it is proper that the employees in Sekretariat of Denpasar Mayor Office give the best performance to the society. Satisfaction from the public means that employees in the Secretariat of the Denpasar Mayor's Office have shown good work performance, concern for the institution and responsible for the assigned tasks. The purpose of this study was to find out what influenced the performance of contract employees at the Secretariat of the Denpasar Mayor's Office. This research is done in Secretariat of Denpasar Mayor Office. The sample used were 34 people with the test of research instrument using validity test and reliability test. Analytical technique used multiple linear regression analysis. The result shows that leadership, motivation, work environment have positive and significant influence on job satisfaction of contract employee at Sekretariat Kantor Walikota Denpasar. Leadership is a dominant variable that affects the job satisfaction of contract employees at the Secretariat of Denpasar Mayor's Office. Keywords : leadership, motivation, environment and job satisfaction